Technostress mitigation: an experimental study of social support during a computer freeze - Christoph Weinert; Christian Maier; Sven Laumer; Tim Weitzel (Journal of Business Economics, 2020)
In situations when Information Systems (IS) do not work as intended, using IS might hinder their users and let them perceive technostress; this then comes along with reduced user performance and high perceptions of exhaustion, among others. To alleviate these consequences, a mitigating behavior of stressed users is to seek social support to get instrumental (e.g., from the help desk) or emotional (e.g., consolation) backing. Using insights from psychology literature that suggest social support reduces the consequences of stressors, this paper investigates how instrumental and emotional support reduces the consequences of techno-stressors, such as reduced end-user performance, techno-exhaustion, and physiological arousal, caused by techno-unreliability such as a computer freeze. In a laboratory setting, measurements of skin conductance were used to evaluate the technostress of 73 subjects, manipulated by techno-unreliability and then treated with instrumental and emotional support. The findings indicate that social support increased end-user performance as well as reduced techno-exhaustion and physiological arousal. In particular, instrumental support directly influenced end-user performance, techno-exhaustion, and physiological arousal, whereas emotional support only influenced techno-exhaustion. Further, this study provides the first indications that the effect of social support on technostress depends on individual differences.
Keywords: M15; O33; 650; Instrumental and emotional support; Techno-unreliability; End-user performance; Exhaustion; Arousal; Skin conductance